2019
DOI: 10.1007/s40520-019-01248-w
|View full text |Cite
|
Sign up to set email alerts
|

Five-year longitudinal changes in thigh muscle mass of septuagenarian men and women assessed with DXA and MRI

Abstract: Magnetic resonance imaging (MRI) and dual-energy X-ray absorptiometry (DXA) were used to assess changes in thigh lean mass in septuagenarian men and women during a 5-year longitudinal study. Twenty-four older individuals participated in the study (10 men: 71.6 ± 4.1 years; 14 women: 71.3 ± 3.2 years at baseline). Thigh MRI and whole-body DXA scans were used to estimate changes in thigh lean mass. Both MRI and DXA showed that thigh lean mass was reduced by approximately 5% (P = 0.001) over the 5-year period in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…In septuagenarian individuals, Delmonico et al [ 14 ] demonstrated an annual decrease in muscle area of − 4.9 ± 7.4% in men and of − 3.4 ± 7.9% in women after > 5 years of follow up. A similar result was found by Cameron et al [ 15 ] also in septuagenarian recreationally active men and women, in whom the decrease in thigh lean mass assessed by magnetic resonance imaging (MRI) and whole body lean mass assessed by dual energy x-ray absorptiometry (DXA) was approximately 5% during 5 years. These changes in muscularity have been termed sarcopenia by Irwin Rosenberg in 1988, which comes from Greek and means sarx = flesh and penia = loss [ 16 ].…”
Section: Sarcopenia: Definition Etiology Operational Criteria and Methods Of Assessmentsupporting
confidence: 84%
“…In septuagenarian individuals, Delmonico et al [ 14 ] demonstrated an annual decrease in muscle area of − 4.9 ± 7.4% in men and of − 3.4 ± 7.9% in women after > 5 years of follow up. A similar result was found by Cameron et al [ 15 ] also in septuagenarian recreationally active men and women, in whom the decrease in thigh lean mass assessed by magnetic resonance imaging (MRI) and whole body lean mass assessed by dual energy x-ray absorptiometry (DXA) was approximately 5% during 5 years. These changes in muscularity have been termed sarcopenia by Irwin Rosenberg in 1988, which comes from Greek and means sarx = flesh and penia = loss [ 16 ].…”
Section: Sarcopenia: Definition Etiology Operational Criteria and Methods Of Assessmentsupporting
confidence: 84%
“…A study by Delmonico et al [ 12 ], conducted on 1678 subjects (heterogeneous for age, sex and ethnicity), showed that from 70 years of age there is an annual reduction of the muscular area of 4.9 ± 7.4% in men and 3.2 ± 7.9% in women. Similar results were obtained by Cameron et al [ 13 ] in a population of seventy, in which lean mass was measured with magnetic resonance imaging (MRI) and dual-energy X-ray absorptiometry (DXA). The loss of MM was approximately 5% in five years of follow-up regardless of basal MM values.…”
Section: Introductionsupporting
confidence: 83%
“…A longitudinal study conducted on Caucasian men over the age of 70 years showed that in fat-free mass there was a decrease of about 0.5-0.8% per year (Kemmler et al, 2019). In line with this, other studies show that a decrease also occurs in the muscle mass of the thighs of both men and women aged 70 years (Cameron et al, 2020).…”
Section: Introductionmentioning
confidence: 70%